Técnicas de estimulación cognitiva y abordaje temprano de la depresión en un paciente - Luna Suarez, Mayron Shadan (2019)
The present research work is focused on cognitive stimulation techniques and how they influence the early approach in depression of an adult, having as a starting point the conceptualization of the two variables and defining them, thus being the stimulation techniques those strategies that allow to potentiate the cognitive abilities in the patient, allowing him to modify his negative or distorted thoughts and exchange them for more positive ones. Techniques such as observation, interview and a psychometric test were also used, in addition to having the file or medical history provided by the psychological department of the Technical University of Babahoyo. Within the situations detected, significant data were presented regarding the case and the problem throughout the process, but through the application of strategies and a therapeutic plan based on CBT, positive results were achieved